Efficient Photosynthetic Functioning of Arabidopsis thaliana Through Electron Dissipation in Chloroplasts and Electron Export to Mitochondria Under Ammonium Nutrition - Podgórska, Anna; Mazur, Radosław; Ostaszewska-Bugajska, Monika; Kryzheuskaya, Katsiaryna; Dziewit, Kacper; Borysiuk, Klaudia; Wdowiak, Agata; Burian, Maria; Rasmusson, Allan G.; Szal, Bożena (Frontiers in Plant Science, 2020)
An improvement in photosynthetic rate promotes the growth of crop plants. The sink-regulation of photosynthesis is crucial in optimizing nitrogen fixation and integrating it with carbon balance. Studies on these processes are essential in understanding growth inhibition in plants with ammonium (NH4+) syndrome. Hence, we sought to investigate the effects of using nitrogen sources with different states of reduction (during assimilation of NO3- versus NH4+) on the photosynthetic performance of Arabidopsis thaliana. Our results demonstrated that photosynthetic functioning during long-term NH4+ nutrition was not disturbed and that no indication of photoinhibition of PSII was detected, revealing the robustness of the photosynthetic apparatus during stressful conditions. Based on our findings, we propose multiple strategies to sustain photosynthetic activity during limited reductant utilization for NH4+ assimilation. One mechanism to prevent chloroplast electron transport chain overreduction during NH4+ nutrition is for cyclic electron flow together with plastid terminal oxidase activity. Moreover, redox state in chloroplasts was optimized by a dedicated type II NAD(P)H dehydrogenase. In order to reduce the amount of energy that reaches the photosynthetic reaction centers and to facilitate photosynthetic protection during NH4+ nutrition, non-photochemical quenching (NPQ) and ample xanthophyll cycle pigments efficiently dissipate excess excitation. Additionally, high redox load may be dissipated in other metabolic reactions outside of chloroplasts due to the direct export of nucleotides through the malate/oxaloacetate valve. Mitochondrial alternative pathways can downstream support the overreduction of chloroplasts. This mechanism correlated with the improved growth of A. thaliana with the overexpression of the alternative oxidase 1a (AOX1a) during NH4+ nutrition. Most remarkably, our findings demonstrated the capacity of chloroplasts to tolerate NH4+ syndrome instead of providing redox poise to the cells.